ANALISA CEMARAN LOGAM MERKURI PADA IKAN AIR LAUT DAN UDANG SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Yosy Cinthya Eriwaty Silalahi; Jon Kenedy Marpaung; Supartiningsih Supartiningsih (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Mercury is a heavy metal that can have a toxic effect on the body so it can cause death. Mercury metal contamination in food is regulated in SNI number 7387 of 2009 regarding the Maximum Heavy Metal Limit. Some metal waste disposal ends up in rivers, lakes, or sea waters so that metal pollution can occur in the ecosystem. This study aims to determine levels of mercury metal contamination in seawater fish, including shark, mackerel, salmon, tuna, red snapper, and white shrimp. Sample preparation was carried out by wet digestion method using a microwave digestion device. Mercury analysis was carried out using the AAS (Atomic Absorption Spectrophotometry) method. The wavelength used is 253.7 nm. The results showed that mercury in sharks was 0.2045 ± 0.0099 mg/kg, mackerel 0.4184 ± 0.0297 mg/kg, salmon 0.3848 ± 0.0794 mg/kg, tuna fish 0.3706 ± 0.0674 mg/kg, snapper 0.4088 ± 0.0397 mg/kg, and shrimp 0.4289 ± 0.0813 mg/kg. The results of the analysis showed that of the six samples of seawater fish that had been tested, the maximum metal contamination limit determined by SNI 7387 the Year 2009 was 0.5 mg/kg.